(3EOGQI QGS GdeGd GdYGe (B/s - (3cGaj, jhSa eUWais ((3bSfWjfI(B: s (3CdaG ddhKGFb(B, s, 2017)
(3eGgjI GdEOGQI GdfbOjI (B-(3eaghe GdJOabGJ hCgejJgG (B-(3JNWjW GdfbOjI (B-(3CSGdjH GOGQI GdJbOjI (B-(3JMOjO GdQUjO GdfbOj GdefGSH (B-(3GOGQI QGS GdeGd GdYGed (B-(3GdaTd hGdJYKQ GdeGdj aj GdTQcGJ (B-(3GOGQI SjhdI GdfbOjI (B-(3eDTQGJ caGAI QGS GdeGd GdYGed hGdJMdjd GdeGdj ddSjhdI (B-(3GdJMdjd GdeGdj dCZQGV GdJfHD HGdaTd GdeGdj (B-(3GOGQI eRjL GdGSJKeGQGJ GdeDbJI (B-(3JNWjW MSGHGJ GdbHV(B((3ELQGAGJ efM GdGFJeGf(B) -(3GOGQI GdeNRhf(B:(3JMOjO GdCOfi ddeNRhf hGdQbGHI Ydi GdeNRhf (B-(3GOGQI GdNUhe GdeJOGhd ceUOQ dJehjd GdCUhd GdeJOGhdI(B-(3eUGOQ GdJehjd bUjQI GdCLd(B.s
(3HHdjhZQGajG(B:(3U(B.295s
Keywords: (3GdSjhdI GdfbOjIs